The assessment of etiology and risk factors of urinary tract infections in geriatric patients admitted to emergency department - Nazik, Selçuk; Hakkoymaz, Hakan (Journal of Surgery and Medicine, 2022)
Background/Aim: A urinary tract infection (UTI) is one of the most common bacterial infections in the elderly population. This study aimed to evaluate the etiology and risk factors of UTI among patients aged 65 and over who were admitted to the emergency department and then hospitalized. Methods: This study was designed as a descriptive epidemiological study. Data of patients aged 65 and over, who were admitted to the adult emergency department of Kahramanmaraş Sütçü İmam University Medical Faculty and hospitalized between October 2015 and October 2018 with a diagnosis of UTI, were included in the study. Study data were collected through a retrospective scan of the patient files from the automated hospital system. Results: Of the patients, 51% (n = 50) were female, and 49% (n = 48) were male. Of the patients diagnosed with UTI, 68.4% were aged 75 years or older. Fever, flank pain, and dysuria were found to be among the main reasons for patients with UTI to present to the emergency department. The most common risk factors for UTI were found to be the presence of diabetes mellitus and immunosuppression. Benign prostatic hyperplasia and nephrolithiasis were found to be the most common risk factors in males. In 83.7% of the patients, urine cultures were obtained at the initial presentation, and Escherichia coli was found to be the most common microorganism in patients with positive urine cultures. Conclusion: The presence of UTI causes an increase in the risk of mortality in geriatric patients. Therefore, UTI should be considered in the differential diagnosis when the general condition has deteriorated in the geriatric patient even if the patient is asymptomatic. Urine culture samples should be obtained in cases of suspected infection, and antibiotic therapy should be started immediately to decrease mortality and increase recovery rates when the urine results indicate infection.